FA-6 Analysis of Sperm Freezing Capability of Various Bulls at the Singosari AI Center - Rhesti Indriastuti; Enniek Herwiyanti; Anny Amaliya; Iis Arifiantini; Bambang Purwantara (Hemera Zoa, 2018)
Artificial insemination (AI) has been widely applied to improve genetic quality in cattle worldwide. One of the most important factors in AI program is the quality of semen. Many procedures in semen processing have been developed to preserve the sperm quality. The Singosari AI center produces the frozen semen through cryopreservation method. During this process, the number of semen collected will be rejected if the quality is low. Fresh semen with less than 70% of sperm motility, before freezing semen with less than 55%of sperm motility and less than 40% of sperm post-thawing motility evaluation will be rejected, so that it was only the viable sperm will be processed to be frozen semen commercial. Therefore, comparative study was carried out to analyze the freezing capability of sperm.